The Effect of Financial Ratio and Firm Size on Stock Return in Property and Real Estate Companies Listed on the Indonesia Stock Exchange - Nurhaida Hafni Dian S (The Indonesian Accounting Review, 2018)
This research aims to fi nd out the effect of fi nancial ratios and fi rm size on stock return. The object of this research is property and real estate companies listed on the Indonesia Stock Exchange 2012-2016. The independent variables used in this study are fi nancial ratios, consisting of liquidity, profi tability, activity and leverage, and fi rm size, while the dependent variable is stock return. The sampling technique is conducted using purposive sampling method. Data analysis method used is multiple linear regression analysis. The results of this study show that leverage has a signifi cant effect on stock return, but liquidity, profi tability, activity but fi rm size has no effect on stock return.